Quinine associated cerebella ataxia responded with Rehabilitative therapy- A case report from a resource limited country Tanzania (Tanzania Medical Journal, 2019)
BackgroundQuinine is among the commonly used drugs against malaria and it has been found to have effects against the central nervous system. The most contemporary documented effect is to the cerebellum. Its toxins can affect the layers of the cerebellum molecular (outermost layer), purkinje (middle) and granular layer (innermost). One of the observed effects is ataxia. Despite its effect, it is commonly used in our settings for treatment of complicated malaria.Case presentationA previously well-known 23-years old female, who is a local, second year medical student, presented to the town-based, district-level hospital with a two-day history of headache, joints pain, generalized body malaise, and vomiting. She did not travel to any endemic areas. During her clinical examination, she was noted to be febrile at 38’c. Examination on the central nervous system, cardio respiratory system was unremarkable. Blood slide for malaria parasite revealed 3mps/200wbc. The full blood picture findings were within the normal range except for the granulocytes which were slightly elevated. She was admitted and then injected with 600mg of Quinine (I.V) 8 hourly for 3 days and after she had finished the dose she started swaying with staggering gait. The condition worsened hence leading to a transfer to a resourceful centre for possible Magnetic resonance imaging (MRI). MRI could not depict any lesion in the brain neither the spinal cord. Neuro-rehabilitation was done and eventually after fourteen days the patient recovered. Conclusion Administration of quinine injection may have adverse effects on the postural and balance related structures of the brain. However, the resulting loss of balance and ataxia may resolve with time and with physical therapy. This case report ought to remind medical personnel attending patients especially those suffering from Malaria to be careful and observe the recommended dosage as it may compromise or cause effects to central nervous system. It also reminds urgent referral cases to opt for rehabilitation if undesired effects to the central nervous system occur.Keywords: Quinine, cerebellum, ataxia, rehabilitation.